Challenges and Dilemmas for Dental Undergraduate Teaching with the Advent of COVID-19 - João Henrique Lara do Amaral; Andrea Clemente Palmier; Marcos Azeredo Furquim Werneck; Simone Dutra Lucas; Maria Inês Barreiros Senna (Association of Support to Oral Health Research (APESB), 2021)
Since the 1980s, the development of neoliberalism has been observed in Brazil, which has led to the progressive weakening of public policies (including those of education) and the population's impoverishment. In the field of education, there was an increase in the privatization of higher education, inadequate to the requirements of national development, characterizing it more as a commodity than as a right. This article aims to discuss some challenges, risks, and possible strategies to face the impact of the COVID19 pandemic in undergraduate dental education. This pandemic had an immediate and dramatic impact on dental education in more than 130 countries, prompting teachers and students to adopt remote teaching activities. In Brazil, theoretical classes were offered remotely, mainly in private institutions where there was an intensification of academic work for both teachers and students. This process requires support in technological and pedagogical aspects, including tools, resources, and training courses. In the resumption of clinical education, changes in biosafety actions are being proposed to preserve the health of the actors involved. The application of these measures will imply a great mobilization of students, teachers, and technicians and extra attention so that the constitutive dimensions of the teaching-learning process in health are not minimized or forgotten.